Blockchain in logistics and production from Blockchain 1.0 to Blockchain 5.0: An intra-inter-organizational framework - Choi, Tsan-Ming; Siqin, Tana (Transportation research. Part E, Logistics and transportation review, 2022)
•Discuss the evolution of blockchain: from Blockchain 1.0 to Blockchain 5.0.•Examine the current states of knowledge in the adoption of blockchain in logistics and production.•Build the intra-inter-organizational (IIO) framework.•Propose research agenda for future explorations. Blockchain technology is a ground breaking disruptive technology in production and logistics systems. However, how it affects logistics and production over the past years as well as what should be examined next remain unclear. This paper fills this gap by first discussing the evolution of blockchain (from Blockchain 1.0 to Blockchain 5.0). Then, we examine the related production and logistics management literature and highlight the current states of knowledge in the field. We review in more details the analytical and empirical studies and uncover the research methods, topics, insights and implications. After that, with references to both the examined literature and observed industrial practices, we identify various important research gaps one by one. We build the intra-inter-organizational (IIO) operational framework to highlight the importance of both internal (i.e., intra-organizational level) and inter-organizational considerations in order to adopt blockchain successfully in production and logistics systems. Critical factors for implementing blockchain under the IIO framework are uncovered. Finally, based on the IIO framework, a future research agenda, which relates to the different stages of blockchain development as well as different topical areas, is established.